Using Brain spect with trodat in the Diagnosis of Substance Addiction (2016)
Introduction: the implementation of functional neuroimaging in the study of various neurological and psychiatric disorders allowed the use thereof as technique in the study of substance-related disorders. This research included the use of nuclear medicine tools in order to contribute to the diagnosis of people with illegal psychoactive substance dependence. Materials and methods: A descriptive cross-sectional study was conducted on eight cases of patients between 18 and 44 years with known clinical disorder diagnosis due to dependence to multiple psychoactive substances, according to the dsm iv-tr criteria, which used the outpatient service of Clínica San Miguel Arcángel in Cartago, Colombia, in 2011. A perfusion brain spect imaging was implemented with trodat - 99mtc and the presence of different toxins in urine was confirmed through a multi drug method. Results: In the studies made with perfusion brain spect imaging with trodat - 99mtc, a reduction was found in the uptake of radiopharmaceutical in the base cores, in a bilateral and asymmetric manner with greater involvement of the putamen, compared to studies made in healthy individuals. Conclusion: The findings in this population of patients with substance dependence showed hypocaptation in the base nuclei through the implementation perfusion brain spect imaging with trodat - 99mtc, suggesting that this methodology could provide technical and scientific arguments to make positive or negative diagnoses on substance addiction.